INDIAN BANKING SYSTEM AND ECONOMIC DEVELOPMENT: AN ANALYTICAL STUDY - SHAH CHIRAGKUMAR; Dr. DIVYANG JOSHI (The Bioscan, 2024)
In its capacity as the central authority, the Reserve Bank of India is responsible for overseeing a wide variety of financial institutions. These institutions include those in the public and private sectors, as well as those in rural and regional areas, and cooperative banks. The banking industry has seen a tremendous diversification and expansion that has never been seen before, which is unusual in the framework of its historical setting. Bank assets make up more than 80 percent of the total assets held by the financial sector in the majority of developing nations, which is a far higher proportion than what is observed in industrialised economies. Nearly two-thirds of the assets held by banks are concentrated in the five primary financial institutions in the majority of developing market nations. The majority of these banks are nationwide in scope. The numbers are far lower in developed economies. An further factor that differentiates the banking sectors of industrialised nations and those of developing countries is the degree to which banking activities are internationalised through internationalisation. Emerging nations usually have much lower degrees of internationalisation, which may be evaluated by the proportion of their total assets that are owned by banks that are owned by foreign firms on average. Having said that, this pattern does not appear to be relevant in every single place of the world. Over the course of the last several decades, the financial industry has seen a number of significant shifts. The shift that has taken place in the kind of organisations that are currently prevalent is among the most important. In the 1980s, a great number of financial institutions expanded their operations, with some of them culminating in the formation of major conglomerates that had branches all across the country. In this article, the changes and advancements that have occurred in the banking sector in India are discussed.